Interculturalism in Schools: a study on teaching practice in the Pibid - Andréa Rosana Fetzner (Universidade Federal do Rio Grande do Sul, 2018)
The study analyzes interculturalism and its contributions to the teaching practices in elementary schools in Brazil. Its aim was to identify, within the practices described in the reports of the Programa Institucional de Bolsa de Iniciação à Docência - Pibid, didactic doings that demonstrate particular commitment to learning situations that have focused on dialogue, polyphony and originality of insights on the topics under study. The conclusion brings some possibilities, understood as being intercultural, for teaching practices at school.